Matched - Book 1 - Condie, Allyson Braithwaite (New York Dutton Books, 2010)
All her life, Cassia has never had a choice: The Society dictates everything, including when and how to play, where to work, where to live, what to eat and wear, when to die, and most importantly to Cassia as she turns 17, whom to marry. When she's matched with her best friend Xander, things couldn't be more perfect, but why did her neighbor Ky's face show up on her match disk as well?
Keywords: Mate selection -- Juvenile fiction; Triangles (Interpersonal relations) -- Juvenile fiction; Self-realization -- Juvenile fiction; Mate selection -- Fiction; Triangles (Interpersonal relations) -- Fiction; Self-realization -- Fiction; Fantasy